The Implementation Of Teaching English Vocabulary Using Total Physical Response At The Fifth Grade Of Sdn 2 Bonagung In 2014/2015 Academic Year - Ratna Sari, Desy, Drs. Djoko Srijono, M.Hum, Siti Fatimah, S.Pd. M.Hum (2015)
The objective of this study is to describe the implementation of teaching English vocabulary using Total Physical Response and to describe the result of the implementation of teaching English vocabulary using Total Physical Response at the fifth grade of SDN 2 Bonagung in 2014/2015 academic year. This research is descriptive research. The data are collected from the classroom observation of teaching vocabulary using TPR and pictures in the classroom. The writer get source of the data are event, informant, and document. The method of collecting data is observation, interview, and document. The technique for analyzing data is reduction of the data, display of the data, conclusion and verification. The result shows that: (1) the goal of teaching English vocabuary using Total Physical Response especially at the fifth grade is to help the students receive and memorize vocabulary easily in English; (2) The materials of teaching are based on syllabus and the materials in teaching learning is taken from internet and textbook; (3) the teacher goes through the process that consist of 6 stages ; review, new commands, other items introduced, physical respond, role reversal, reading and writing; (4) the teacher holds three roles. Those roles are teacher as drillmaster, teacher as director, teacher as motivator; (5) the learners holds two roles. Those roles are the learners as listener and as performer; (6) ) the result of the implementation very good. The writer analyzes the result of data with comparing between the result of the daily test and observation of the students response.The average score of daily test is 81.5 and observation score is 74.